Hubungan Kadar Serum Glutamat Piruvat Transaminase (Sgpt) Dan Kadar Trigliserida Pada Pasien Penyakit Jantung Koroner - Mirdayanti Mirdayanti; Dita Ellyana Artha; Husniyati Yahya (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2018)
The research has been done about the correlation of serum glutamic pyruvic transaminase (SGPT) concentration and triglyceride concentration on coronary heart disease patient at Dr. WahidinSudirohusodo Hospital. The aim of this research is to know the correlation of SGPT and triglyceride concentration. Cross-sectional research method study on 35 samples using Enzymatic Colorimetric method.Population Characteristic by men with 62.9% and women with 37.1%.The lawest age on 48 years old and the highest age on 74 years old. Biggest population in age 51-60 year with a total of 48.57%. The total research subject with normal SGPT serum concentration is 71.4% and SGPT serum concentration is 62.85% and high triglyceride concentration is 37.15%. Statistical analysis using the Pearson Correlation Test shows that r = 0.536 (r value 0-1) so we can conclude that SGPT concentration and TG concentration have a significant correlation.